On the Hunt for New Toxin Families Produced by a Mediterranean Strain of the Benthic Dinoflagellate Ostreopsis cf. ovata - Eva Ternon; Evgenia Glukhov; Emily Trytten; Rodolphe Lemée; William H. Gerwick (Toxins, 2022)
Ostreopsis cf. ovata is a benthic dinoflagellate known to produce palytoxin (PLTX) and its analogues. Recent investigations suggested the production of unknown toxins by a Mediterranean strain. In the present work, two new families of toxins, potentially novel in their structures, were purified from this same Mediterranean strain of Ostreopsis cf. ovata. The low amount of material isolated only allowed for acquisition of high-resolution mass spectrometry data and the evaluation of their cytotoxicity to human lung cancer cells. Based on their HRMS data, none of these new compounds appear to be close PLTX analogues, although their mass spectra suggest poly-hydroxylated long chain compounds of high molecular weight (1370–2143 Da). The cell cytotoxicity concentrations (CC50) of these new purified toxins ranged between 0.68 and 3.12 µg/mL, and this was enhanced when they were tested as mixtures, suggesting synergistic effects of Ostreopsis toxins. The two families of compounds were named the liguriatoxins (LGTX) and rivieratoxins (RVTX), with each family containing three members. Additional work on purification is needed to fully characterize the structures of these six new dinoflagellate toxins.